1984
DOI: 10.1115/1.3269143
|View full text |Cite
|
Sign up to set email alerts
|

The Vibrational Behavior of a Multi-Shaft, Multi-Bearing System in the Presence of a Propagating Transverse Crack

Abstract: The effects of a transverse crack on the dynamics of a multi-rotor, multi-bearing system have been studied experimentally using a spin rig. It is concluded that except for very large cracks, the vibrational behavior is similar to that of a slotted shaft with additional excitation due to the crack opening and closing. It confirms the theory, described elsewhere, that it is possible to calculate the behavior of a cracked and/or slotted rotor for a realistic turbogenerator model for crack depths sufficient to giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 0 publications
1
49
0
4
Order By: Relevance
“…To reduce the difficulty of the problem in the study of cracked shafts, researchers often assumed that the amplitude of the vibrations due to the presence of cracks is weak compared to those of the vibrations due to permanent loads [El Arem and Nguyen 2006;Gasch 1976;Mayes and Davies 1976;1980;Davies and Mayes 1984;Henry and Okah-Avae 1976;Gasch 1993]. The present model is more general and allows us to overcome the limitations of such an assumption.…”
Section: Discussionmentioning
confidence: 97%
“…To reduce the difficulty of the problem in the study of cracked shafts, researchers often assumed that the amplitude of the vibrations due to the presence of cracks is weak compared to those of the vibrations due to permanent loads [El Arem and Nguyen 2006;Gasch 1976;Mayes and Davies 1976;1980;Davies and Mayes 1984;Henry and Okah-Avae 1976;Gasch 1993]. The present model is more general and allows us to overcome the limitations of such an assumption.…”
Section: Discussionmentioning
confidence: 97%
“…Various theoretical and experimental works [3][4][5][6][7][8][9][10] performed over the last three decades have indicated that the change in modal properties (natural frequencies and modes shapes) may be useful for the detection of a crack, as well as for the identification of both crack depth and location. Moreover, the influence of opening and closing of crack due to the shaft self-weight for various orientations of the shaft has been investigated [3,11] and showed the effectiveness of the change in natural frequencies versus the orientation of the shaft to detect the orientation of the crack front.…”
Section: Introductionmentioning
confidence: 99%
“…Inagaki [7], Mayes [8], and Nelson [9] investigated a general rotor system with a transverse crack using methods such as the transfer matrix method, and finite element method. Some of them [7,10] performed experiments using a test rotor and compared with theoretical results. The propeller-bearing-shaft system has been holistically modeled using FE procedure with the actual in-situ profiles for the propeller, bearings, supports and torque loading aluminum arm.…”
Section: Detection Of Cracks In Rotor Shaftmentioning
confidence: 99%